Silicophytoliths from a Pampean native tree community (Celtis ehrenbergiana community) and their representation in the soil assemblage - de Rito, Mara Victoria (2018)
Plant phytolith production and their incorporation into soil assemblages has been studied by diverse authors in different regions of theworld,mainly in the Northern Hemisphere and Africa. However, these types of studies are scarce in native plant communities from South America, especially in non-grass communities. The comprehension of the relation between plant phytolith production and their incorporation into soils is crucial for the interpretation of past environments and vegetation based on fossil phytolith records. The aim of this work is todescribe the silicophytolith production of a Pampean native tree community (Celtis ehrenbergiana community) and the silicophytolith assemblages of the soils, in order to understand the relation between silicophytolith production and their incorporation in these natural forests. Silicophytoliths from 19 species of these communitieswere extracted through a calcination technique; while soil samples were subjected to routine techniques. Soil silicophytoliths were counted and described, and their abundances were referred in relation to total soil mineralogy. Morphologies were similar between species and were mainly derived from the epidermal, vascular and sclerenchymatic tissues. Celtis spp. produced abundant diagnostic morphologies, such as cystoliths and platelet echinate silicophytoliths, typical of the genus. Soil assemblages were dominated by grass silicophytoliths and in a lesser proportion by dicotyledons silicophytoliths. However, grasses are scarcely found or absent in actual forests. These results showed that there was not a direct relation between plant silicophytolith production and soil phytolith incorporation in these forests. As it occurs in different environments worldwide, soil silicophytoliths are affected by taphonomical processes (fragmentation, dissolution, mobilization, etc.) and they are not always an exact reflection of phytolith production of local plants. These results indicate that a high silicophytolith production in plants (in this case Celtis spp.) is not always reflected in soil assemblages. These aspects should be considered in relation to the interpretation of fossil silicophytolith records.